2015
DOI: 10.1016/j.cogpsych.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

What makes us think? A three-stage dual-process model of analytic engagement

Abstract: The distinction between intuitive and analytic thinking is common in psychology. However, while often being quite clear on the characteristics of the two processes ('Type 1' processes are fast, autonomous, intuitive, etc. and 'Type 2' processes are slow, deliberative, analytic, etc.), dual-process theorists have been heavily criticized for being unclear on the factors that determine when an individual will think analytically or rely on their intuition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

47
505
5
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 372 publications
(584 citation statements)
references
References 130 publications
47
505
5
8
Order By: Relevance
“…To disentangle between the two possibilities, we computed the response times for nonoptimal and optimal responses to conflict trials and compared them with the response time for optimal responses to no-conflict trials (e.g., De Neys, 2012;De Neys & Bonnefon, 2013;De Neys & Glumicic, 2008;Pennycook et al, 2015). In both experiments, optimal responses to conflict trials took longer than optimal responses to no-conflict trials, confirming the successful conflict inhibition and override of the heuristic answer across high-and low-bias reasoners.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To disentangle between the two possibilities, we computed the response times for nonoptimal and optimal responses to conflict trials and compared them with the response time for optimal responses to no-conflict trials (e.g., De Neys, 2012;De Neys & Bonnefon, 2013;De Neys & Glumicic, 2008;Pennycook et al, 2015). In both experiments, optimal responses to conflict trials took longer than optimal responses to no-conflict trials, confirming the successful conflict inhibition and override of the heuristic answer across high-and low-bias reasoners.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found no evidence of conflict detection in case of error, because response times for nonoptimal responses to conflict trials and optimal responses to noconflict trials did not differ. In light of the three-stage process model (Pennycook et al, 2015), it could be argued that the pairs of ratios that compose the trials of the ratio-bias task often cue two initial responses that are in conflict to each other in conflict trials: a ratio-bias response (preference for the largest numerator) and a logically correct response (preference for the largest ratio), even if the first one is likely to come to mind more fluently than the latter. Whenever this conflict is detected, participants engage in cognitive decoupling, inhibiting and overriding the more fluent heuristic response to give the logically correct response (Stanovich, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mevel et al, 2014;Pennycook, Fugelsang & Koehler, 2015), we also calculated the number of heuristic responses given by each participant on conflict problems, and categorized each of the 128 participants who made at least one heuristic response as either "majority heuristic" (3 or 4 heuristic responses out of four, 53 participants) or "minority heuristic" (1 or 2 heuristic responses, 75 participants). We entered this measure as a participant-level predictor in our models, but found that it was not involved with any interactions in the analyses above (t's < 1, p's > .4).…”
mentioning
confidence: 99%